The bronze panel (paliotto) of San Moisè in Venice: materials and causes of deterioration. Issue 2 (10th April 2015) - Chiavari, C.; Martini, C.; Montalbani, S.; Franzoni, E.; Bignozzi, M.C.; Passeri, M.C.
Abstract : This paper reports on the diagnostic investigations on the bronze panel in the Church of San Moisè in Venice (Italy), aiming at the identification of materials and causes of corrosion. Both the bulk metal and surface layers were investigated by a wide range of techniques: alloy composition and microstructure were determined by VP‐SEM/EDS, the corrosion products by Raman spectroscopy and XRD. The organic compounds were analysed by pyrolysis gas chromatography mass spectrometry (Py‐GC‐MS). The adjacent mortars were analysed in terms of mineralogical composition and soluble salts content, in order to highlight their role in the degradation processes at the contact areas between the masonry and the bronze panel. The alloy is a quaternary bronze (Cu‐Sn‐Zn‐Pb): high‐relief figures were cast separately then mechanically joined to the panel. Traces of the clay core were detected in the back of the panel. The bronze surface was artificially patinated by potassium sulphide. The organic protective layer consisted of stearin and paraffinic wax. However, siccative oil was detected at the interface with the metal, likely corresponding to the original protective treatment. Also pine resin traces were detected. The corrosion products mainly consisted of basic copper chlorides (paratacamite, atacamite) and mixed copper/sodium carbonates (chalconatronite), deriving from the interaction with mortar.